2022
DOI: 10.1021/acscatal.2c02779
|View full text |Cite
|
Sign up to set email alerts
|

Improving Oxygen Reduction Reaction Performance via Central Ions Enhanced Crystal-Field Splitting of MnO6 Octahedron

Abstract: This study reported manganese oxide octahedral molecular sieves (OMS-2) with the substitution of potassium ions in the tunnels by alkaline-earth metal ion doping. The results showed that OMS-2 doped with barium ions, whose ionic radius was closest to potassium ions, had the best oxygen reduction activity. The addition of barium ions largely occupied the original positions of potassium ions, resulting in the change of the exposed crystal planes, which changed the adsorption of oxygen. Further research found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…Within the same potential region, the percentage of peroxides of all hierarchical CSC-based MnO x electrodes was drastically decreased to less than 9% compared with that of CSC-based electrodes. Based on the above results, it can be concluded that at the CSCs/MnO x -based electrocatalysts, the ORR proceeds via an apparent 4-electron reduction mechanism, wherein molecular oxygen is reduced first to hydroperoxide (HO 2 – ), which is subsequently reduced to hydroxide in concordance with the behavior of α-MnO 2 electrocatalyst toward the ORR in an alkaline electrolyte. , …”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Within the same potential region, the percentage of peroxides of all hierarchical CSC-based MnO x electrodes was drastically decreased to less than 9% compared with that of CSC-based electrodes. Based on the above results, it can be concluded that at the CSCs/MnO x -based electrocatalysts, the ORR proceeds via an apparent 4-electron reduction mechanism, wherein molecular oxygen is reduced first to hydroperoxide (HO 2 – ), which is subsequently reduced to hydroxide in concordance with the behavior of α-MnO 2 electrocatalyst toward the ORR in an alkaline electrolyte. , …”
Section: Resultsmentioning
confidence: 76%
“…Based on the above results, it can be concluded that at the CSCs/ MnO x -based electrocatalysts, the ORR proceeds via an apparent 4-electron reduction mechanism, wherein molecular oxygen is reduced first to hydroperoxide (HO 2 − ), which is subsequently reduced to hydroxide in concordance with the behavior of α-MnO 2 electrocatalyst toward the ORR in an alkaline electrolyte. 54,55 Beneficial effects of functionalized CSCs to MnO x were more impressive with regard to the OER. Indeed, the capacitance-corrected voltammetry curves of the OER in Figure 4e show that at the maximum potential of 1.76 V, the faradaic current densities of CSCs/MnO x , Func CSCs-0.2M/ MnO x , and Func CSCs-2M/MnO x were 0.81, 1.64, and 6.49 mA cm −2 , respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The H-MnO 2 sample displays main diffraction peaks at 2θ = 12.7°, 18.3°, 28.7°, 37.5°, 56.7°, and 60.2°, which are indexed to the (110), (200), (310), (211), (501), and (521) facets of MnO 2 (JCPDS 29-1020), respectively. Furthermore, the weak signals of (110) and (200) facets suggest poor crystallinity, which is easy to degrade in vivo . The diffraction signal is similar before and after coating with membrane, suggesting the structure of H-MnO 2 is robust (Figure e).…”
Section: Resultsmentioning
confidence: 94%
“…The tumor volume was calculated through the formula described below. 200) facets suggest poor crystallinity, 42 which is easy to degrade in vivo. 43 The diffraction signal is similar before and after coating with membrane, suggesting the structure of H-MnO 2 is robust (Figure 3e).…”
Section: Cm−h-mno 2 −Sor In Vitro Drug Release Assaymentioning
confidence: 99%
“…[5] Generally, the external cations and water molecules are inserted into the 2 × 2 tunnels for charge balance or structure stability, which has aroused great interest in the research field of catalysis and energy storage. [6][7][8] Yuan et al reported that the presence of tunnel cations of K + in the 𝛼-MnO 2 not only improves electronic conductivity through electron hopping via Mn 3+ /Mn 4+ couples but also enhances Li + diffusivity. [6] Such K + presence in the tunnels of 𝛼-MnO 2 enhances the electrochemical performances on Li/𝛼-MnO 2 based batteries.…”
Section: Introductionmentioning
confidence: 99%